Africa's International Rivers : An Economic Perspective - Sadoff, Claudia W.; Whittington, Dale; Grey, David (Washington, DC: World Bank, 2013)
Cooperative management, and development of Africa's international rivers holds real promise for greater sustainability, and productivity of the continent's increasingly scarce water resources, and fragile environment. Moreover, the potential benefits of cooperative water resources management, can serve as catalysts for broader regional cooperation, economic integration, and development - and even conflict prevention. But riparians will pursue joint action only when they expect to receive greater benefits through cooperation than through unilateral action. Economic analysis can be used to make the case for cooperation on international rivers, using tools that will help identify, and measure the potential incremental benefits of cooperation, determine the distribution of benefits among riparians, and assess the feasibility, and fairness of alternative management, and investment scenarios. Where such schemes yield benefit distributions, not perceived as equitable among riparians, economic tools could also be used to calculate, design, and implement arrangements for redistribution. In all of these ways, economics can play an important role in enabling the management of international rivers, helping to motivate, design, and implement cooperative water resources management.